2014
DOI: 10.1161/hypertensionaha.114.03456
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation and Kidney Injury Molecule-1–Associated Proximal Tubule Injury in Severe Preeclampsia

Abstract: We enrolled 25 cases with severe preeclampsia, 25 controls with chronic hypertension, and 25 healthy controls without hypertension from a cohort of women receiving care at Brigham and Women's Hospital from March 2012 through March 2013. Institutional review board approval was obtained through the Partners Human Research Committee, and subjects gave informed consent. All procedures followed were in accordance with institutional guidelines. Methods Abstract-Kidney injury with proteinuria is a characteristic feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 71 publications
1
21
1
Order By: Relevance
“…On the other hand, both severe preeclampsia and lupus have been associated with increased terminal complement activation as measured by plasma and urine biomarkers C5a and sC5b-9 (Burwick et al, 2013; Chiu et al, 1998; Gou et al, 2013). In preeclampsia, urinary excretion of sC5b-9 correlates most closely with kidney injury molecule 1 (KIM-1), a marker of proximal tubule injury (Burwick et al, 2014b). Extrinsic C5 activation by serine proteases in the coagulation cascade may also contribute to increased levels of C5a and sC5b-9 in severe preeclampsia (Amara et al, 2010; Burwick et al, 2014a; Huber-Lang et al, 2006).…”
Section: Complement Deficiencies and Pregnancymentioning
confidence: 99%
“…On the other hand, both severe preeclampsia and lupus have been associated with increased terminal complement activation as measured by plasma and urine biomarkers C5a and sC5b-9 (Burwick et al, 2013; Chiu et al, 1998; Gou et al, 2013). In preeclampsia, urinary excretion of sC5b-9 correlates most closely with kidney injury molecule 1 (KIM-1), a marker of proximal tubule injury (Burwick et al, 2014b). Extrinsic C5 activation by serine proteases in the coagulation cascade may also contribute to increased levels of C5a and sC5b-9 in severe preeclampsia (Amara et al, 2010; Burwick et al, 2014a; Huber-Lang et al, 2006).…”
Section: Complement Deficiencies and Pregnancymentioning
confidence: 99%
“…Multiple studies demonstrated significantly enhanced systemic complement system activation in preeclamptic pregnancies compared to normal pregnancies (Derzsy et al, 2010; Regal et al, 2015a). Both the placenta and kidney also showed evidence of increased local complement activation in preeclampsia, coincident with up-regulation of message for complement regulators but no evidence of changes in regulator expression using immunohistochemistry have been reported (Burwick et al, 2014; Buurma et al, 2012; Lokki et al, 2014; Penning et al, 2015). However, the event or events that initiate complement activation in preeclampsia are unknown.…”
Section: Introductionmentioning
confidence: 97%
“…However, the exact significance and underlying mechanism are far from clear. Increased urinary complement activation products (CAPs) have been reported in proteinuric kidney diseases including DN [6][7][8][9][10][11][12] . However, the exact significance of urinary CAPs in DN is still unclear.…”
Section: Introductionmentioning
confidence: 99%